The organoleptic and nutritional characteristics of innovative high-fiber khalas date-based bar - Barakat, Hassan; S.M. Almutairi, Abdulkarim (Italian Journal of Food Science, 2024)
Making functional and nutritionally balanced date bars is of innovative concern. The current study intends to create a novel high-fiber and nutritious Khalas date-based bar (KDBB). The proximate composition, mineral contents, sugar profile, amino and fatty acids profile, volatiles and phytochemicals, antioxidant activity, and an in vitro digestion of protein and carbohydrates for bar formula containing 50% Khalas dates (KD) were investigated. Results indicated that protein, fat, ash, fiber, available carbohydrates, and vitamin C were 9.34, 4.93, 2.05, 8.01, 54.04 g 100 g-1, and 16.67 mg, respectively. Potassium, magnesium, phosphorus, and calcium were present in abundance. Sucrose had the highest sugar concentration at 246.35 mg g-1. Total phenolic content (TPC) was 547.19 mg gallic acid equivalent 100 g-1, giving 719.39 and 815.98 µmol of Trolox equivalent (TE) 100 g-1 for 2,2-diphenylpicrylhy-drazyl radical scavenging activity (DPPH-RSA) and 2,2’-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS)-RSA, respectively. Total carotenoids, flavonoids, and flavonols were 327.19 mg 100 g-1, 998.25 mg quercetin equivalent 100 g-1, and 749.57 mg QE 100 g-1, respectively. The highest discovered phenolics, flavonoids, and isoflavone were pyrocatechol (10249.73 μg g-1), catechin (193.50 μg g-1), and daidzein (18.77 μg g-1), respectively. Lysine was the highest among the essential amino acids. Saturated and unsaturated fatty acids were 43.73% and 56.27%, respectively. The omega-6 fatty acid, cis-8,11,14-eicosatrienoic, was predominant with a 31.08% valuation. The gas chromatography–mass spectrometry analysis identified 17 compounds, with a predominant presence of 9,12-octadecadienoyl chloride (38.13 g 100 g-1). The glycemic index (GI) of KDBB was 39.97, which was lower than KD’s score (54.12). In conclusion, prepared KDBB could present a good idea for consuming dates and the based products with high fiber content and lower GI. Scaling up such products could be helpful to health-conscious individuals.